Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1744-6198.2007.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Case Study Review of Role Transition in Community Nursing

Abstract: The results of this investigation revealed themes derived from data collection, including autonomy, client and family, education, and community as nursing work. This study indicated that making the transition to community-based nursing includes conceptual as well as emotional adjustments. Community nursing practice was seen by the participants as nursing that captures a holistic approach incorporating multiple dimensions from psychological, sociological, economic, and physical to spiritual aspects that provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 12 publications
3
31
0
1
Order By: Relevance
“…These findings are supported by evidence that nurses are increasingly being attracted to take up positions in PHC, with the number of nurses working in Australian general practices increasing from around 8000 nationally in 2009 to almost 12,000 in 2012 (AIHW ). Similar trends of a growing PHC nursing workforce have also been reported internationally (Zurmehly ).…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…These findings are supported by evidence that nurses are increasingly being attracted to take up positions in PHC, with the number of nurses working in Australian general practices increasing from around 8000 nationally in 2009 to almost 12,000 in 2012 (AIHW ). Similar trends of a growing PHC nursing workforce have also been reported internationally (Zurmehly ).…”
Section: Introductionsupporting
confidence: 82%
“…, Simpson et al . , Zurmehly , Holt ), with exceptions being Bryan et al . 's () quantitative survey and Hartung's () mixed methods study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2. Nursing administration and practices: Zurmehly (2007) indicated that making the transition to community-based nursing includes conceptual as well as emotional adjustments. Study results indicate a need for additional supportive preparation strategies to be incorporated into nursing orientation and continuing education programs.…”
Section: Resultsmentioning
confidence: 99%